Superior Semicircular Canal Dehiscence Syndrome – Diagnosis and Surgical Management - Palma Diaz, Marite; Cisneros Lesser, Juan Carlos; Vega Alarcón, Alfredo (International Archives of Otorhinolaryngology, 2017)
Introduction Superior semicircular canal dehiscence syndrome was described by Minor et al in 1998. It is a troublesome syndrome that results in vertigo and oscillopsia induced by loud sounds or changes in the pressure of the external auditory canal or middle ear. Patients may present with autophony, hyperacusis, pulsatile tinnitus and hearing loss. When symptoms are mild, they are usually managed conservatively, but surgical intervention may be needed for patients with debilitating symptoms.Objective The aim of this manuscript is to review the different surgical techniques used to repair the superior semicircular canal dehiscence.Data Sources PubMed and Ovid-SP databases.Data Synthesis The different approaches are described and discussed, as well as their limitations. We also review the advantages and disadvantages of the plugging, capping and resurfacing techniques to repair the dehiscence.Conclusions Each of the surgical approaches has advantages and disadvantages. The middle fossa approach gives a better view of the dehiscence, but comes with a higher morbidity than the transmastoid approach. Endoscopic assistance may be advantageous during the middle cranial fossa approach for better visualization. The plugging and capping techniques are associated with higher success rates than resurfacing, with no added risk of hearing loss.
Keywords: superior semicircular canal; superior semicircular canal dehiscence; vertigo; middle cranial fossa